Principles and Bases of Peaceful Coexistence in Light of Quran - Kiani, Tal’at; Kiani, Rasoul; Karimpour, Naeim; Khodadadi, Seiyed Abedin; Yousefi, Samad (Journal of History Culture and Art Research, 2017)
The contemporary world witnesses many accusations regarding the compatibility of Islam and peaceful coexistence. Many people base their arguments by relying on secondary sources or exceptional cases through history for this accusation. Media, especially Western one, highlights and dramatizes some negative behaviors of Muslim people even though they do not represent whole Islamic world and Islamic theology. This investigation addresses principles and bases of peaceful coexistence according to Quran. It highlights the Islamic viewpoint according to Quran. For this purpose, related verses are classified and indexed. The study suggests that Quran encourages Muslims for peaceful coexistence with non-Muslim people.